Instability of asymptotically anti-de Sitter black holes under Robin conditions at the timelike boundary - Araneda, Bernardo Gabriel (2017)
The static region outside the event horizon of an asymptotically anti-de Sitter black hole has a conformal timelike boundary I on which boundary conditions have to be imposed for the evolution of linear fields from initial data to be a well-posed problem. Only homogeneous Dirichlet, Neumann or Robin conditions preserve the action of the background isometry group on the solution space. We study the case in which the modal decomposition of the linear field leads to potentials not diverging at the conformal timelike boundary. We prove that there is always an instability if Robin boundary conditions with large enough γ (the quotient between the values of the derivative of the field and the field at the boundary) are allowed. We explain the origin of this instability, show that for modes with non-negative potentials there is a single unstable state and prove a number of properties of this state. Although our results apply, in general, to 1+1 wave equations on a half-infinite domain with a potential that is not singular at the boundary, our motivation is to analyze the gravitational stability of the four-dimensional Schwarzschild anti-de Sitter black holes in the context of the black hole nonmodal linear stability program initiated in Phys. Rev. Lett. 112, 191101 (2014)PRLTAO0031-900710.1103/PhysRevLett.112.191101, and the related supersymmetric type of duality exchanging odd and even modes. We prove that this symmetry is broken except when a combination of Dirichlet conditions in the even sector and a particular Robin condition in the odd sector is enforced, or vice versa, and that only the first of these two choices leads to stable dynamics.